"Regoaling": A useful tool for improved patient/parent communication in pediatric dermatology. Issue 3 (11th March 2019) - Waldman, Reid A.; Waldman, Steven D.; Grant‐Kels, Jane M.
Abstract: "Regoaling" is a term for the process by which patients and their families develop new care and life‐related goals in response to changes in an individual's medical condition. While this term draws its roots from the pediatric critical and palliative care literature where it has been developed to provide a path to assist families in transitioning their child's care goals, regoaling has the potential to be a very important communication tool for pediatric dermatologists who are the primary managers of chronic, unrelenting skin diseases in children. Herein, we introduce the concept of regoaling to pediatric dermatology and provide practical advice on how and when to assist patients and their families with regoaling.